2021
DOI: 10.3389/fphar.2020.619265
|View full text |Cite
|
Sign up to set email alerts
|

Tryptamine Attenuates Experimental Multiple Sclerosis Through Activation of Aryl Hydrocarbon Receptor

Abstract: Tryptamine is a naturally occurring monoamine alkaloid which has been shown to act as an aryl hydrocarbon receptor (AHR) agonist. It is produced in large quantities from the catabolism of the essential amino acid tryptophan by commensal microorganisms within the gastrointestinal (GI) tract of homeothermic organisms. Previous studies have established microbiota derived AHR ligands as potent regulators of neuroinflammation, further defining the role the gut-brain axis plays in the complex etiology in multiple sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 56 publications
1
22
0
Order By: Relevance
“…The detection of the cytokines was performed using ELISA MAX standards kits from Biolegend. The staining of cells for dual markers was performed as described in our previous publications (Al-Ghezi et al, 2019;Becker et al, 2020;Dopkins et al, 2020;Mohammed et al, 2020b). In brief, MNCs and spleen cells were treated with Fc Block reagent (BD Pharmingen, San Diego, CA) followed by staining cells with various antibodies by incubation at 4°C for 20-30 min.…”
Section: Detection Of Cytokines In Serummentioning
confidence: 99%
“…The detection of the cytokines was performed using ELISA MAX standards kits from Biolegend. The staining of cells for dual markers was performed as described in our previous publications (Al-Ghezi et al, 2019;Becker et al, 2020;Dopkins et al, 2020;Mohammed et al, 2020b). In brief, MNCs and spleen cells were treated with Fc Block reagent (BD Pharmingen, San Diego, CA) followed by staining cells with various antibodies by incubation at 4°C for 20-30 min.…”
Section: Detection Of Cytokines In Serummentioning
confidence: 99%
“…The calculated binding energies for stizolamine, vicine, convicine, L-cystine, wyerone acid, jasmonic acid, tuberonic acid, and wyerone epoxide against the AhR are provided for the first time. In the case of the products of biotransformation, except for tryptamine (98), m-tyramine (99), equol (100), baicalein (101), and taxifolin (102), the rest of the molecules lack reports addressing this subject. For comparative purposes, Table 1 shows our calculated binding affinities for all molecules along with a reference of its biotransformation.…”
Section: Exploring the Metabolic Fate Of Phytochemicals In Broad Bean...mentioning
confidence: 99%
“…Regarding the metabolic fate of the selected compounds, the AhR-binding ability of tryptamine (98), an L-tryptophan microbiome derivative (84) was calculated as −5.95 kcal/mol. Hence, it is also consistent with the literature and highlights the reliability of the implemented method.…”
Section: Exploring the Metabolic Fate Of Phytochemicals In Broad Bean...mentioning
confidence: 99%
“…It is interesting to note that microbiota-derived AhR ligands can also serve as potent regulators of neuroinflammation, further characterizing the role for AhR in the gut-brain axis in suppressing MS progression. For example, a recent study suggested that tryptamine administration attenuates EAE by activating AhR and suppressing neuroinflammation [ 129 ]. Tryptamine treatment also caused alterations in the gut microbiota and promoted butyrate production [ 129 ].…”
Section: Ahr and Inflammatory Diseasesmentioning
confidence: 99%
“…For example, a recent study suggested that tryptamine administration attenuates EAE by activating AhR and suppressing neuroinflammation [ 129 ]. Tryptamine treatment also caused alterations in the gut microbiota and promoted butyrate production [ 129 ]. Tryptophan metabolites produced by the intestinal microbiota along with type I interferons activate AhR in astrocytes and lead to suppression of inflammation [ 180 ].…”
Section: Ahr and Inflammatory Diseasesmentioning
confidence: 99%